PENERAPAN ANALISIS SWOT DALAM MENINGKATKAN PENJUALAN “SIOMAY PAK BLANGKON”JEMBER - Dinarso, Rahmat Cahyo; Haryono, Rudi; Dharma, Rendra Adi; Kusuma, Hendra; Qomariah, Nurul (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
The increasingly fierce level of business competition currently means that business actors need to have a strategy in order to survive and develop. Companies and micro businesses need to implement effective marketing strategies to increase sales. This marketing strategy can also prepare yourself to face increasingly fierce competition from other competing businesses. By using a SWOT analysis, a business can determine what needs to be improved both internally and externally to ensure work operations run smoothly. This research aims to see the application of SWOT analysis to the factors that influence sales and to analyze the application of SWOT analysis in increasing the sales volume of "Siomay Pak Blangkon". The method used in this research is a literature review method using a qualitative descriptive writing system and an interview method by directly interviewing the owner of "Siomay Pak Blangkon". The results of the research show that with this SWOT analysis the strengths, weaknesses, opportunities and threats of Jember's "Siomay Pak Blangkon" micro business actors can be described. The strengths include: there are 2 dumpling menus, wet and dry, guaranteed quality, offline and online sales. The weaknesses are: short selling time, still using sidewalks for selling. The opportunities are: increasing population of Jember city, being able to sell online, strategic location. Meanwhile, the threats are: the emergence of new business actors, less stable economic conditions. Keywords: SWOT analysis; marketing strategy; sale; micro business.